2015
DOI: 10.1080/21620555.2014.990328
|View full text |Cite
|
Sign up to set email alerts
|

It’s Not Just About the Money: Gender and Youth Migration from Rural China

Abstract: Statistics suggest that young men and women in China migrate at almost equal numbers, but we know less about gender differences in the decision to migrate. We examine the factors associated with the decision to migrate and the rationales given by young migrants. Our results are consistent with previous figures and show no overall gender differences in susceptibility to migration. However, we find that sibship structure operates differently on the decisions of boys and girls. Young men were more likely to repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 58 publications
4
27
0
Order By: Relevance
“…Gender dynamics may also dictate whether youth migrate, the extent to which parents invest in further opportunities, and experiences at the destination (Chiang, Hannum, and Kao 2015). Though the ratio of male to female migrants in the region is relatively equal, migration dynamics may differ (Global Migration Group 2014).…”
Section: Youth Migration: a Family-based Strategymentioning
confidence: 99%
“…Gender dynamics may also dictate whether youth migrate, the extent to which parents invest in further opportunities, and experiences at the destination (Chiang, Hannum, and Kao 2015). Though the ratio of male to female migrants in the region is relatively equal, migration dynamics may differ (Global Migration Group 2014).…”
Section: Youth Migration: a Family-based Strategymentioning
confidence: 99%
“…First, our research contributes to the gender and employment inequality literature. Concentrating on married women migrant workers, a rapidly increasing group in recent years and who are often ignored in the literature (Chang 2010), our research provides a more fine grained picture of the work experiences of migrant women. Many studies conducted since the 1990s focused on young single migrant women (Chiang, Hannum and Kao 2015; Gaetano and Jacka 2004;Jacka 2006;Lee 1998;Pun 2005;Wallis 2013); however, employment inequality for married women migrant workers has been largely neglected.…”
Section: Contributionsmentioning
confidence: 99%
“…Early research on China's women migrant workforce resembles the literature on women and migration more generally. Research conducted since the 1990s focused extensively on the experiences of young, single migrant women (see Chiang, Hannum and Kao ; Gaetano and Jacka ; Jacka ; Lee ; Pun ; Wallis ) and it was assumed that ‘they will return to the village after a few years to get married, have children and take over domestic duties and agriculture’ (Jacka , 135). Especially for rural Chinese women, social and other costs resulting from their absence from the rural family were key factors in decisions to migrate (Cooke ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That the economic and non-economic motives motivate women to work has been investigated by Chiang et al (2013). Using the method of embedded case study, they found that married women work for economic and non-economic motives.…”
Section: ))mentioning
confidence: 99%